Semiotic approach to the notion of radial consumption - Bendezú Untiveros, Raúl (1993)
The title of this article refers to consumption, not reception. This alludes to a pragmatic and intersubjective dimension; that one to an economic dimension and to questions of market and value. Today communication is an economic good subject to a system of supply and demand, as well as a good with a symbolic value thanks to which it enters the universe of representations and symbolic uses made by a society, thus giving it its value and its objectivity. We can think that consuming a fungible economic good, like consuming radio as a means of communication, are activities that lead to conceptions rooted in our sensoriality and in our experience.